Association of nesfatin-1 level with body composition, dietary intake and resting metabolic rate in obese and morbid obese subjects. Issue 4 (October 2015) - Mirzaei, Khadijeh; Hossein-nezhad, Arash; Keshavarz, Seyed Ali; Koohdani, Fariba; Eshraghian, Mohammad Reza; Saboor-Yaraghi, Ali Akbar; Hosseini, Saeed; Chamari, Maryam; Zareei, Mahnaz; Djalali, Mahmoud
Abstract: Aims: Nesfatin-1 identified neuroendocrine peptide is involved in regulation of homeostasis via modulation of metabolism, energy homeostasis and food intake. We aimed to investigate the associations of circulating nesfatin-1 level with food intake, body composition and resting metabolic rate (RMR) and also examine the correlation between circulating peroxisome proliferator-activated receptor gamma (PPARγ) and nesfatin-1 levels in obese and morbid obese subjects. Methods: A total of 96 obese subjects (including 18 morbid obese subjects) were participated in the current cross-sectional study. We assessed the body composition with the use of Body Composition Analyzer . RMR was measured by means of the MetaCheck ™, an instrument designed to measure RMR using indirect calorimetry. All baseline blood samples were obtained following an overnight fasting. Plasma concentrations of nesfatin-1 and circulating PPARγ were measured with the use of an ELISA method. Statistical analyses were performed using SPSS. Results: We found significant associations between fat percent and circulating nesfatin-1 in obese and morbid obese subjects. There was main association between circulating nesfatin-1 and PPARγ concentration in obese subjects and it was more strong association in morbid obese participants. There was marginally significant differences between percent predicted RMR between different categorized nesfatin-1 levels. There were also higher intakes of calorie, carbohydrate and protein in obese group who had lower concentration of nesfatin-1. Conclusions: Our data indicated the fat percent as main determinant factor in circulating nesfatin-1 level. It appears nesfatin-1 and PPARγ might be concurrently involved in adipogenesis pathway.